2018
DOI: 10.1016/j.ebiom.2018.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Activation of mTORC1 signaling in gastric X/A-like cells induces spontaneous pancreatic fibrosis and derangement of glucose metabolism by reducing ghrelin production

Abstract: BackgroundPancreatic fibrosis is a pathophysiological process associated with excessive deposition of extracellular matrix in pancreas, leading to reduced insulin secretion and derangement of glucose metabolism. X/A-like cells, a group of unique endocrine cells in gastric oxyntic mucosa, produce and secret ghrelin to influence energy balance. Whether gastric X/A-like cells affect pancreatic fibrosis and subsequent glucose homeostasis remains unclear.MethodsWe established a Ghrl-cre transgene in which the cre e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…These findings are supported by several in vitro studies showing that mTOR signaling is activated in the presence of increased intracellular ATP levels [ 52 ]. In pathological states, increased activity of the mTOR signaling has been associated with obesity [ 39 ] and, accordingly, the knockout mice for the mTOR downstream S6kinase 1 are protected against diet-induced obesity [ 53 ].…”
Section: Gut–brain Axismentioning
confidence: 99%
See 3 more Smart Citations
“…These findings are supported by several in vitro studies showing that mTOR signaling is activated in the presence of increased intracellular ATP levels [ 52 ]. In pathological states, increased activity of the mTOR signaling has been associated with obesity [ 39 ] and, accordingly, the knockout mice for the mTOR downstream S6kinase 1 are protected against diet-induced obesity [ 53 ].…”
Section: Gut–brain Axismentioning
confidence: 99%
“…It was reported that the components of the mTOR pathway are expressed in different endocrine cells, including X/A-like cells and with lower expression in G cells [ 54 ]. Specifically, in X/A-like cells, one of the most abundant types of gastric endocrine cells, the mTOR pathway is involved in the secretion of different gastrokines with a relevant role in metabolism regulation such as ghrelin and nesfatin-1 [ 53 ]. Consequently, this pathway has been proposed as a component of the gut–brain axis by modulating the gastric production of different stomach-derived signals involved in energy homeostasis [ 49 , 50 , 51 ].…”
Section: Gut–brain Axismentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, although the stomach and pancreas are physically connected and share common autonomic innervations, very few humoral mechanisms have been described by which the stomach impacts the exocrine pancreas. It is thus noteworthy that Yu et al [ 1 ], as reported in EBioMedicine , have identified a novel gastric-pancreas humoral axis active in health.…”
mentioning
confidence: 99%